2022
DOI: 10.1021/acs.jpcb.2c01764
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Growth of Urea and Its Modulation by Additives as Analyzed by All-Atom MD Simulation and Solution Theory

Abstract: The crystal growth of urea was analyzed with all-atom molecular dynamics (MD) simulation for the (001) and (110) faces in contact with aqueous solutions. The local environment of a crystallizing molecule was treated in terms of the numbers of crystalline neighbors and the orientation relative to the crystal surface, and the molecular-level inhomogeneity of a growing surface was addressed by decomposing the overall rate of growth into a sum of the contributions conditioned by the local structure and orientation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 81 publications
(172 reference statements)
0
3
0
Order By: Relevance
“…The assumed error of the induction time is 2 frames, which translates into 0.4 s. Within these 2 frames, the detection delay between the nucleation and a detectable crystal size is included. The growth rate of the (001) growth mode is simulated with 0.02 nm/ns . The detectable size with this setup is ≥ 1mm which is smaller than the size of a crystal growing for 0.4 s. From the distribution of the number of pulses required to induce crystallization, the probability of induction is extracted (see the Supporting Information for a detailed explanation of the evaluation).…”
Section: Experimental Setup Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The assumed error of the induction time is 2 frames, which translates into 0.4 s. Within these 2 frames, the detection delay between the nucleation and a detectable crystal size is included. The growth rate of the (001) growth mode is simulated with 0.02 nm/ns . The detectable size with this setup is ≥ 1mm which is smaller than the size of a crystal growing for 0.4 s. From the distribution of the number of pulses required to induce crystallization, the probability of induction is extracted (see the Supporting Information for a detailed explanation of the evaluation).…”
Section: Experimental Setup Materials and Methodsmentioning
confidence: 99%
“…The growth rate of the (001) growth mode is simulated with 0.02 nm/ ns. 27 The detectable size with this setup is ≥ 1mm which is smaller than the size of a crystal growing for 0.4 s. From the distribution of the number of pulses required to induce crystallization, the probability of induction is extracted (see the Supporting Information for a detailed explanation of the evaluation). The maximum illumination time was 10 min; if crystal induction was not observed in that time, then nucleation was deemed unsuccessful.…”
Section: ■ Introductionmentioning
confidence: 99%
“…74,86 Recently reported all-atom MD simulations confirmed that the modulation of the growth rates of the (0 0 1) and (1 1 0) faces in the presence of biuret, acetone and dimethylformamide correlates with the adsorption free energy of the respective additive. 75 Rizvi et al studied the influence of biuret on the urea morphology as a function of supersaturation in ethanol. 87 Biuret suppresses the growth of the (1 1 1) face more strongly than the growth of (1 1 0) in line with its much stronger interaction with the former.…”
Section: Low-molecular Weight Organic Additivesmentioning
confidence: 99%